2016
DOI: 10.1177/0013916515612254
|View full text |Cite
|
Sign up to set email alerts
|

A Contextual Look at Safe Routes to School Implementation in Texas

Abstract: In an effort to understand factors influencing the implementation and outcomes of the Safe Routes to School (SRTS) program in Texas, interviews were conducted in 2014 with 34 community-and state-level stakeholders involved in the 2007 SRTS grant program. Participants were asked a series of multiple-choice and open-ended questions about SRTS program planning, implementation, and sustainability. Transcribed responses were organized and grouped according to thematic elements using standard qualitative methods. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Of particular interest, many studies emphasized the importance of having long term follow-ups given that implementation of complex AST interventions may require a substantial amount of time [ 17 20 , 43 , 46 ]. Similarly, qualitative evaluations focusing on the implementation of AST interventions also identify lack of time as a key challenge [ 63 , 64 ]. To address the issue of follow-up length, some authors suggested that granting agencies should be encouraged to provide more long term funding [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of particular interest, many studies emphasized the importance of having long term follow-ups given that implementation of complex AST interventions may require a substantial amount of time [ 17 20 , 43 , 46 ]. Similarly, qualitative evaluations focusing on the implementation of AST interventions also identify lack of time as a key challenge [ 63 , 64 ]. To address the issue of follow-up length, some authors suggested that granting agencies should be encouraged to provide more long term funding [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, qualitative evaluations focusing on the implementation of AST interventions also identify lack of time as a key challenge [ 63 , 64 ]. To address the issue of follow-up length, some authors suggested that granting agencies should be encouraged to provide more long term funding [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More pointedly, Mammen, Stone, Buliung, and Faulkner (2015) examined the perspectives of STP facilitators in the Canadian context and reported that collaboration, an organized model structure, and member involvement positively impacted implementation; subsequently, they called for future case studies to examine STPs in greater depth. Atteberry et al (2016) and Cooper and McMillan (2010), meanwhile, examined the implementation of the Safe Routes To School program in the U.S. context, with the former, more recent paper recommending future work investigate the interactions of members within the partnerships and their implications for intervention implementation. Here, we present a detailed evaluation case study of the organizational features shaping the implementation and sustainability of an AST intervention (the STP model) from the perspectives of stakeholders involved, as well as a first attempt to understand AST intervention dynamics using organizational change theory.…”
Section: [Insert Figure 1 Here]mentioning
confidence: 99%